2004
DOI: 10.2175/193864704784342596
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Fecal Coliforms after Anaerobic Digestion and Dewatering

Abstract: In August of 2001, the largest known installation of a phased temperature anaerobic process at a 60-MDG wastewater treatment plant was placed into operation. The facility met the time and temperature requirement for Class A biosolids. Testing of the biosolids following thermophillic/anaerobic digestion followed by mesophilic/anaerobic digestion revealed no detectable levels of fecal coliform bacteria in the treated biosolids. However, subsequent testing of the biosolids following dewatering by high solid centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 1 publication
(1 reference statement)
1
10
0
Order By: Relevance
“…Improved culturability of bacteria due to the shear applied in centrifuges (Cheung et al, 2003;Qi et al, 2007), false positive results associated with enumeration techniques (Qi et al, 2004), contamination from the centrifuge (Hendrickson et al, 2004), the effect of floc break up on improved culturability (Cheung et al, 2003), removal of growth inhibitors during dewatering (Qi et al, 2007) and effect of day-light throughout the storage of biosolids (Gö zen and Ö rmeci, 2010) have been investigated as the potential factors that promote bacterial 1,00E+00 w a t e r r e s e a r c h 4 7 ( 2 0 1 3 ) 4 2 8 e4 3 8 regrowth. However, none of these factors has been found to be correlated with the bacterial regrowth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Improved culturability of bacteria due to the shear applied in centrifuges (Cheung et al, 2003;Qi et al, 2007), false positive results associated with enumeration techniques (Qi et al, 2004), contamination from the centrifuge (Hendrickson et al, 2004), the effect of floc break up on improved culturability (Cheung et al, 2003), removal of growth inhibitors during dewatering (Qi et al, 2007) and effect of day-light throughout the storage of biosolids (Gö zen and Ö rmeci, 2010) have been investigated as the potential factors that promote bacterial 1,00E+00 w a t e r r e s e a r c h 4 7 ( 2 0 1 3 ) 4 2 8 e4 3 8 regrowth. However, none of these factors has been found to be correlated with the bacterial regrowth.…”
Section: Resultsmentioning
confidence: 99%
“…Biological activity is reduced along with the organic matter content of sludge during anaerobic digestion. However, it has recently been reported that significantly higher densities of Fecal Coliform and/or Escherichia coli have been measured in dewatered cake samples compared to the samples collected after anaerobic digestion (Hendrickson et al, 2004;Iranpour et al, 2003;Cheung et al, 2003;Monteleone et al, 2004;Qi et al, 2004). This finding is more pronounced in the centrifuge dewatered sludge cakes rather than in belt filter dewatered cakes (Cheung et al, 2003;Erdal et al, 2003;Hendrickson et al, 2004;Higgins et al, 2007;Qi et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many have reported higher fecal coliform (FC) populations, on a dry solids basis, in centrifugally dewatered biosolids compared to the digester effluents (Iranpour et al, 2002(Iranpour et al, , 2003Erdal et al, 2003;Hendrickson et al, 2004;Monteleone et al, 2004;Qi et al, 2004;Cooper et al, 2005. In some cases, populations easily met U.S. EPA Class A biosolids limits prior to dewatering, but failed this standard after dewatering.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been hypothesized (e.g. Hendrickson et al, 2004;Higgins et al, 2007) that an activating substance (such as an autoinducer) is released during centrifugation. Another possibility is that biodegradable organics might be released, or removed, which would affect the population dynamics in the dewatered solids.…”
Section: Introductionmentioning
confidence: 99%